2014
DOI: 10.1007/s11274-014-1787-9
|View full text |Cite
|
Sign up to set email alerts
|

Induction of resistance to S. aureus in an environmental marine biofilm grown in Sydney Harbor, NSW, Australia

Abstract: The study of environmental biofilms is complicated by the difficulty of working with them under lab conditions. Nonetheless, knowledge of cellular activity and interactions within environmental biofilms could lead to novel biomedical applications. To address this problem we previously proposed a new technique for inducing resistance to Staphylococcus aureus in an intact environmental biofilm. In the current follow-up study we applied the new technique in a biogeographically distinct environment using a differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Results showed that inhalable suspended chrysotile near local roads was related to the frequent development of lung cancer in the population of long-term exposed regions. Lafleur et al (2015) deposited S. aureus N315 onto Nuclepore filter with 25 mm diameter and 0.2 µm pore size, which made subsequent assessment easy with image analysis software.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that inhalable suspended chrysotile near local roads was related to the frequent development of lung cancer in the population of long-term exposed regions. Lafleur et al (2015) deposited S. aureus N315 onto Nuclepore filter with 25 mm diameter and 0.2 µm pore size, which made subsequent assessment easy with image analysis software.…”
Section: Introductionmentioning
confidence: 99%